To Suppress or to Mitigate COVID-19: That is the Question - Khan, Anam; Goff, Allyson; Ahmad, Akram; Patel, Isha (Journal of Pharmacy Practice and Community Medicine)
In India, public health experts have been debating the most effective way of combating COVID-19 (or SARS-COV-2 virus) while balancing the amount of lives lost and trying to preserve the economy. This virus is particularly challenging for India as the population is so large, and the healthcare system is still developing to meet the needs of its citizens. While social distancing has been and is being widely practiced worldwide to mitigate the further spread of COVID-19, it is apparent that more aggressive public health measures are needed to further decrease the numbers of infected people. Already, India has extended its lockdown from March 24th to the end of May.[1] By better understanding how this virus propagates, as well as by considering the unique needs of India, experts can better determine the best measures to fight further spread.